New Thio-Compounds and Monoterpenes With Anti-inflammatory Activities From the Fungus Aspergillus sp. CYH26 - Pan, Guojun; Li, Yanling; Che, Xinyu; Tian, Dan; Han, Wenjie; Wang, Zimin; Zhao, Yanfen; Ren, Shuang; Xu, Yiru; Hao, Gangping; Guo, Mengfei; Xiao, Na; et al. (Frontiers in Microbiology, 2021)
Two new thio-compounds named aspergerthinol A and B (1 and 2) and two new monoterpenes named aspergerthinol C and D (3 and 4) were isolated from the endophytic fungus Aspergillus sp. CYH26 from the rhizosphere soil of Cynanchum bungei Decne. The structures of compounds were elucidated by spectroscopic data and quantum NMR and ECD calculations. Compounds 1 and 2 represented a new family of sulfur containing natural products with a 3-methyl-4H-cyclopenta[b]thiophen-4-one skeleton. Compounds 1-4 showed inhibitory activities against NO with IC50 values of 38.0, 19.8, 46.3, and 56.6 μM, respectively.